Antibacterial Modification of Kirschner Wires with Polyluteolin toward Methicillin-Resistant Staphylococcus aureus (MRSA) - Zhu, Jialiang (Materials (Basel), 2015)
In this study we report antibacterial modification of Kirschner wires (K-wires) with polyluteolin (PL) toward methicillin-resistant Staphylococcus aureus (MRSA). K-wires were modified by immersing them in the luteolin-containing aqueous solution for 24 h. Characterizations using scanning electron microscopy and electrochemical methods confirmed the presence of the PL coatings on the K-wires. The PL-coated K-wires were further found to show antibacterial activity toward MRSA and remained unimpaired antibacterial activity even after the steam sterilization treatment.